Synthesis of hierarchically porous mullite ceramics with improved thermal insulation via foam-gelcasting combined with pore former addition. (17th November 2018) - Ge, Shengtao; Lin, Liangxu; Zhang, Haijun; Bi, Yubao; Zheng, Yangfan; Li, Junyi; Deng, Xiangong; Zhang, Shaowei
ABSTRACT: To further improve the thermal insulation performance of porous mullite ceramics used in important industrial sectors, a combined foam-gelcasting and pore-former addition approach was investigated in this work, by which hierarchical porous mullite ceramics with excellent properties, in particular, thermal insulation property, were prepared. Both mesopores (2–50 nm) and macropores (117.8–202.7 μm) were formed in porous mullite ceramics resultant from 2 h firing at 1300°C with various amounts of submicron-sized CaCO3 pore former. The former mainly arose from the decomposition of CaCO3, and the latter from the foam-gelcasting process. The porous samples prepared with CaCO3 addition had low linear shrinkage of 2.35–4.83%, high porosity of 72.98–79.07% and high compressive strength of 5.52–14.82 MPa. Most importantly, they also exhibited a very low thermal-conductivity, e.g. 0.114 W m −1  K −1 at 200°C, which was much lower than in the cases of their counterparts prepared via the conventional foam-gelcasting route.